Peningkatan Hasil Belajar Pendidikan Agama Islam dengan Model Pembelajaran Diskusi Kelompok Kelas X SMA Xaverius Bukittinggi - Muhammad Ridwan (Kampus Akademik Publiser, 2023)
This Classroom Action Research (CAR) was conducted at Xaverius High School Bukittinggi with the subjects of class X E1 students in the odd semester of the 2023/2024 academic year. The problem of this research stems from the low learning outcomes of students in the subject of Islamic Religious Education, especially the material Competing in Goodness and Work Ethics. Of the 32 students, only 40% achieved KKTP 75. Therefore, the researcher applied a group discussion learning model to improve student learning outcomes. The research was conducted in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The results of the study showed an increase in the average student score from 58.75 in the pre-cycle to 68.75 in the first cycle, and increased again to 84.37 in the second cycle. Learning completeness increased from 40% in the pre-cycle, 68% in the first cycle, to 84% in the second cycle. Thus, the application of the group discussion learning model is proven to improve student learning outcomes in the subject of Islamic Religious Education in the class of Xaverius High School Bukittinggi.